The Effect of Labor Migration on the Diffusion of Democracy: Evidence from a Former Soviet Republic - Hillel Rapoport; Andreas Steinmayr; Christoph Trebesch; Toman Omar Mahmoud (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2013)
Migration contributes to the circulation of goods, knowledge, and ideas. Using community and individual-level data from Moldova, we show that the emigration episode that started in the late 1990s strongly affected political preferences and electoral outcomes in Moldova during the following decade and was eventually instrumental in bringing down the last ruling Communist government in Europe. Our results are suggestive of information transmission and cultural diffusion channels. Identification relies on the quasi-experimental context studied and on the differential effects arising from the fact that emigration was directed both to more democratic Western Europe and to less democratic Russia.
Keywords: F22; D72; O1; 330; Emigration; political institutions; elections; social networks; information transmission; cultural diffusion